2015
DOI: 10.1016/j.ejca.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism, interleukin-6 and survival outcomes in patients with advanced ovarian clear cell carcinoma

Abstract: (243 words)Background: We compared survival outcomes and risk of venous thromboembolism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Procoagulant microparticles were found along with venous thromboemboli in cancer patients [258,259]. The impact of IL6 on thrombocytosis has been observed elsewhere and in other cancers [260,261]. …”
Section: Thrombocytosismentioning
confidence: 99%
“…Procoagulant microparticles were found along with venous thromboemboli in cancer patients [258,259]. The impact of IL6 on thrombocytosis has been observed elsewhere and in other cancers [260,261]. …”
Section: Thrombocytosismentioning
confidence: 99%
“…Patients who developed VTE are likely to have an advanced-stage disease or recurrent progressive tumors. 14,38 Current study and others have demonstrated that survival time after VTE are generally poor among patients diagnosed with VTE. 14 This was practically true after recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…This state is marked by increased IL-6 cytokine expression as manifested in patients with type 2 diabetes and hypertension [9,10]. Low dose of omega 3 fish oil used by HIV positive clients have not shown any benefits in reduction of IL-6 expression [11]. Elevated IL-6 expression in chronic conditions is associated with poor progression and clinical outcomes of patients [12,13].…”
Section: Introductionmentioning
confidence: 99%